2012
DOI: 10.1128/jcm.02056-12
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococci Can Persistently Colonize Adult Patients with Chronic Respiratory Disease

Abstract: d; and Consejo Superior de Investigaciones Científicas, Madrid, Spain e Streptococcus pneumoniae plays an important role in causing acute exacerbations in patients with chronic respiratory disease. However, few data are available regarding pneumococcal persistence in adult patients with chronic respiratory diseases. Fifty pneumococci recovered from sputum samples (1995 to 2010) from 13 adult patients with >3 episodes of acute exacerbation or pneumonia, with the same serotype and pulsed-field gel electrophoresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Most of the patients included in the study had severe or very severe COPD, suffering frequent episodes of acute exacerbation and they received multiple antibiotic courses [6]. Although there were no differences in the betalactam consumption among groups, the betalactam resistance rates were higher among relapse episodes.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the patients included in the study had severe or very severe COPD, suffering frequent episodes of acute exacerbation and they received multiple antibiotic courses [6]. Although there were no differences in the betalactam consumption among groups, the betalactam resistance rates were higher among relapse episodes.…”
Section: Discussionmentioning
confidence: 97%
“…We hypothesized that the distribution of pneumococcal serotypes in adults, in both invasive and non-invasive pneumonia, might have changed after the introduction of PCV13 for children [7] and that this distribution may vary depending on the patients' comorbidity and/or risk factors [8]. Given the fact that hospitalization for pneumonia is not decreasing [9] and that S. pneumoniae is the main causative microorganism, updated information will be a key factor for implementing effective strategies to decrease the incidence of CAP.…”
Section: Introductionmentioning
confidence: 99%
“…One phenotype that has not been successfully modeled is the asymptomatic pulmonary colonization that occurs in COPD. Patients are frequently colonized by bacteria within their lungs (5) and can be prone to exacerbations induced by either bacteria or viruses that lead to a rapid deterioration in symptoms (6). A study by Patel et al (7) has shown that the presence of bacteria in the lower airways was associated with an increased frequency of exacerbations.…”
mentioning
confidence: 99%